Larangan Impor Beras dalam Perspektif Hukum Perdagangan Dunia, Hukum Nasional dan Hukum Islam (Mazahib, 2014)
The research on prohibition of rice import in Indonesia, in WTO Agreement, national rules and Islamic law perspective is normative juridical research. The research includes library and field research. The method of analysis is deductive approach, which concludes special characteristic from general explanation. The research purposes are firstly, to know whether application of restriction of rice import is contravene with WTO Agreement, national rules and Islamic law. Secondly, to know if the benefit of members is being nullification or impairment as the result of the application by Indonesian goverment officials on rice import measure. The research concludes that Indonesian measures on rice import (import prohibition and temporary restriction) is not contravene with WTO Agreement and national regulation, because of elimination for agricultural product which necessary to the enforcement of governmental measures which operate to remove a temporary surplus of the like domestic product, by making the surplus available to certain groups of domestic consumers at price below the current market level. The members who have certain effect of restriction, based on article XXII  have opportunity for consultations. When consultations are unsuccessful, the complainant may request the establishment of a panel.  Prohibition rice import is also not contravene with Islamic law, because the purpose to protect local farmers who live in poor is consistent  with Quran word  that God command to maintain justice and kindnes.